Dinamika Pengelolaan Sampah : Studi Kasus Sistem Hanggar di Kabupaten Banyumas - Yuni Tristanti; Eko Hendarto; Edy Suyanto (Pascasarjana Universitas Jenderal Soedirman, 2020)
The waste problem has become an environmental issue in all parts of the world, including the State of Indonesia, especially Banyumas Regency. Waste management in Banyumas Regency has changed, a new paradigm. Starting from the difficulty of land for final processing sites (TPA) to dispose of waste, Banyumas Regency has changed the way it manages its waste. Waste management, which was originally collected-transport-dispose of, was changed in accordance with statutory regulations, namely having to sort the waste from its source. Waste sorting must be carried out in addition to aiming to reduce dependence on large landfills which are now difficult to provide and to achieve the target of the Banyumas District Regional Strategy Policy (Jakstrada), which is to set a target of reducing waste by 30% and handling waste by 70% by 2025. Target A 30% reduction in waste can be achieved by sorting waste by establishing several hangars as centers for sorting community waste. Banyumas Regency has established 5 (five) hangars in 5 (five) areas, namely the Ajibarang hangar, the Sumbang hangar, the Wangon hangar, the Kedungrandu hangar and the Sumpiuh hangar. Waste sorting using the hangar system was chosen because the community considered direct waste sorting to fail, reflecting on the various waste sorting programs that have existed in Indonesia. The hangar establishment in Banyumas Regency aims to provide an example of direct sorting of waste to the community. Activities in the hangar are sorting waste from the community who are its customers with the aim of educating the public about sorting waste so that waste problems can be resolved from the source. Hangar activities carry out reuse, reduce and recycle waste, so that the waste disposed of in the TPA is really residual waste that cannot be used anymore. Based on the research, the hangar actually does sorting of waste but it is not as expected by the Banyumas Regency Government, namely, the residual waste disposed of to the TPA from all hangar activities is still very high, on average above 70% of the total waste that enters the hangar, and The target of reducing waste by 30% by sorting the new waste was achieved at 18.33%.